On the occurrence of weld bead porosity during laser vacuum welding of high pressure aluminium die castings - Teichmann, Fabian; Müller, Sebastian; Dilger, Klaus (Procedia CIRP, 2018)
Procedia CIRP, 74 (2018) 438-441. doi:10.1016/j.procir.2018.08.163
Keywords: Aluminium; Aluminium die castings; Laser vacuum welding; Laser Welding; Porosity; X-ray computed tomography